Towards an energy 'literate' architecture graduate? UK educators' and students' evaluation. (4th July 2018) - Oliveira, Sonja; Marco, Elena; Gething, Bill
ABSTRACT: Whilst calls for upskilling and retraining the UK construction workforce to meet increasingly stringent energy targets are repeatedly documented in construction strategy and policy reports, it remains unclear how higher education, particularly architecture, is responding. The purpose of this paper is to examine how educators and students across UK architecture institutions view energy-related content in their teaching and learning, and how some of the policy initiatives are being approached. The analysis focuses on what educators and students perceive is being taught and how they evaluate issues that need to be 'upskilled' or 'retrained'. This study draws on evaluative practice literature using multiple data sources including focus groups across UK accredited architecture institutions. The research identifies evaluative perspectives that educators and students draw on to discuss views such as personal interests, institutional sovereignty, experience, physical and disciplinary disconnects and an expectation that 'something will change'. Transforming the status quo is perceived as a major obstacle whereby a school design agenda, design studio educators' motivations and a curriculum that only gets added to are shared concerns. The findings enable foundational discussions that will help define recommendations of required educational approaches to 'upskilling' and 'retraining' in a fast-developing international energy policy agenda.